Quaid e azam: sawal jawab ki roshni mein - Anwar, Dawodi (Feroz sons Karachi, 1998)
This is likely a biography or a story about the life of Muhammad Ali Jinnah, the founder of Pakistan. It would likely focus on his contributions to the country and his leadership qualities.